Design of DC-DC Boost Converter with Negative Feedback Control for Constant Current Operation - L Navinkumar Rao; Sanjay Gairola; Sandhya Lavety; Noorul Islam (Institute of Advanced Engineering and Science, 2017)
In this paper design of DC-DC boost converter with constant current control, charging is presented to charge the battery of electric vehicles. The different methods of battery charging are discussed. The charging profile of different types of batteries is investigated and compared with respect to charging time. The battery current is sensed and compared with a reference current and the generated actuating signal which is an error is feed to PI controller to compute a duty cycle of boost converter for constant current operation. A 6 V dc supply is obtained by using a step down transformer and diode rectifier. Boost converter parameters are designed for continuos conduction mode operation. The limiting values of duty cycle are fixed in the range of 0.5 to 0.6 for constant current operation. Simulation is carried out using MATLAB software for constant current operation connected to a 50 Ah, 12 V battery load. The constant current operation is achieved using negative feedback control. The switching frequency of boost converter is set to 20 kHz. The filter components are also designed to reduce ripple content within limited values. The simulation result shows the effectiveness of charging control for hardware implementation.